KUALITAS PELAYANAN PETUGAS PENDAFTARAN RAWAT JALAN TERHADAP PELAYANAN PRIMA DI RUMAH SAKIT: STUDI LITERATUR - Yanasta Yudo Pratama; Sri Wahyunita Mohamad; Tri Ani Marwati; Muhammad Syamsu Hidayat (Politeknik Unggulan Kalimantan, 2022)
The Outpatient Registration Center is a leading service unit which is one part of the medical record task and the place where the patient first meets the officer. Excellent Service, namely the best service provided in accordance with expectations or even exceeding customer expectations. Assessment of service quality through 5 dimensions, namely Ability, Attitude, Attention, Action, and Responsibility. To determine the factors related to the registration service officer of the excellent service in the hospital. Literature search reviewed using the Google Scholar Database with the topic